Fostering Courtesy Through Welcoming Programs: A Case Study in Islamic Education - Saputri, Septia Nur; Kurahman, Opik Taufik (Islamic Religious Education Study Program Postgraduate Program UIN Sunan Gunung Djati Band, 2024)
Developing politeness in students is essential, as it plays a key role in their social interactions. Politeness is a fundamental social norm and has long been a valued cultural trait. To nurture this attitude, Al-Azhar Islamic Junior High School has implemented the welcoming student program. This research aims to explore how the program fosters polite behavior in students. Using a qualitative field study approach with descriptive-qualitative methods, researchers conducted direct observations. The findings indicate that the welcoming student program is effective and efficient in promoting polite behavior. This is evident from students’ habits of speaking respectfully, acting courteously toward others, greeting and smiling at peers, shaking hands with those of the same gender, and clasping hands in greeting with the opposite gender. They are also accustomed to looking down and smiling politely when passing by others.